Nesteroidni antirevmatiki (NSAR) in ledvice - Ravnikar, Andrea (Medicinski razgledi, 2007)
Non-steroidal antiinflammatory drugs (NSAIDs) are among the most widely utilized therapeutic agents today. The main mechanism of their action is via inhibition of cyclooxygenase, the enzyme involved in prostaglandin synthesis. Prostaglandins play a crucial role in the renal circulation when systemic circulation is destabilized or when the blood volume and tive arterial blood volume are compromised. They enable vasodilatation of the renal circulation, renin secretion, and sodium and water excretion. There are two isoforms of cyclooxygenase (COX) (COX-1 or the ĆconstitutiveĆ isoform and COX-2 or the inducible isoform). The inhibition of COX-2, which is normally expressed in activated macrophages and induced by proinflammatory substances, accounts for antiinflammatory, analgesic and antipyretic effects whereas COX-1 suppression causes most side effects, for example gastrointestinal bleeding and ulceration, and platelet dysfunction. It was assumed that selective inhibitionof COX-2 would diminish the wide range of toxic organ effects of nonselective NSAIDs. In the kidney, constitutive expression has been demonstrated for both isoforms. Renal toxicity is therefore similar in nonselective and selective COX-2 inhibitors. Moreover, a number of analyses have suggested that prolonged exposure to selective COX-2 inhibitors increasesthe risk of cardiovascular disease. Renal toxicity associated with the use of NSAIDs can be classified in several distinct clinical syndromesČ acute hemodynamic renal failure, acute tubulointerstitial nephritis with nephrotic syndrome and chronic kidney disease. They differ in the time of druguse that is required for its development, pathogenesis and treatment.
Keywords: Diclofenac; Nefritis intersticijski; Ledvična odpoved; Toxicity; Nephritis, Interstitial; Diklofenak; Kidney Failure; Nefrotični sindrom; drug; Nephrotic Syndrome; zdravila; nesterioidni antirevmatiki; ledvice; nefritis